Textbook Using a Brain Based Learning Model Assisted by a Scientific Approach for Learning Critical Thinking Skills - Amin Harahap; Rohani; Almahdi Rambe; Marzuki Ahmad; Dwi Putria Nasution (Journal of Education Reseach and Evaluation, 2024)
Students' low critical thinking skills are the main problem in this research. Apart from that, in learning it was found that the textbooks used were less varied and did not direct students to develop their thinking abilities. The learning model that can maximize thinking abilities is Brain Based Learning (BBL) and the learning approach that has clear stages and can be included in textbooks is the scientific approach. The aim of this research is to develop a textbook using the BBL model assisted by a scientific approach in teaching students' critical thinking skills. The development model used is the ADDIE Model which includes the stages of analysis, design, development, implementation, evaluation. Research instruments include validation sheets, questionnaires and tests. Research data includes product validation data obtained from expert validation, product response data obtained from student response questionnaire results, and students' critical thinking abilities obtained from tests. The data obtained was analyzed using quantitative and qualitative descriptive techniques. The data analysis carried out showed the results of achieving a Validity Mean Percentage Score (PRS) of 84.74 (valid criteria), the practicality of achieving PRS of 80.59 (practical criteria), and achieving PRS effectiveness of 89.31 (effective criteria). The data analysis carried out shows that the product developed meets the criteria of being valid, practical and effective and is suitable for use as a textbook. Based on these achievements, the development of textbook products with a brain-based learning model is feasible and good for use in teaching students' mathematical critical thinking skills.